Exposure to Electronic Cigarette Advertisements on the Internet and Smoking Behavior in Adolescents - Diah Wijayanti Sutha; Nathratul Ayeshah Binti Zulkifli; Christine Christine; Eka Wilda Faida; Serlly Frida Drastyana; Siti Novianti (Master Program of Health Promotion Faculty of Public Health Diponegoro University, 2026)
Background: E-cigarettes are increasingly popular among adolescents, driven by massive advertising on the internet, especially through social media. These advertisements often display modern and attractive images without including sufficient information about health risks. Social media influencers also play a role in strengthening the appeal of e-cigarettes to adolescents. The purpose of this study is to analyze the relationship between exposure to e-cigarette advertising on the internet and smoking behavior among adolescents in Indonesia.Method: This study used a cross-sectional design with an online survey conducted over three months, from March to June 2024. A total of 625 adolescents aged 14–19 years participated in this study. Respondents reported exposure to e-cigarette advertising on the internet, which was analyzed by age, gender, social media used, and smoking status. Data were analyzed using logistic regression to see the relationship between advertising exposure and smoking behavior.Result The results showed that adolescents who were more frequently exposed to e-cigarette advertising were 2.3 times more likely to try e-cigarettes than those who rarely saw these advertisements. Instagram and YouTube were the main platforms where adolescents were exposed to e-cigarette advertisements. In addition, 50% of respondents reported seeing influencers using e-cigarettes, and 40.2% of them were interested in trying them. Most e-cigarette advertisements were also found not to include clear health warnings. This study confirms that exposure to e-cigarette advertisements on social media plays a significant role in increasing smoking interest and behavior in adolescents. Therefore, stricter regulations are needed for e-cigarette marketing on the internet, including supervision of the role of influencers and the obligation to include health warnings in every advertisement. In addition, broader health education is needed to increase adolescent awareness of the risks of e-cigarettes.